2022
DOI: 10.1111/1750-3841.16250
|View full text |Cite
|
Sign up to set email alerts
|

Palm‐based cellulose nanofiber isolated from mechano‐chemical processing as sustainable rheological modifier in reduced fat mayonnaise

Abstract: Reducing fat intake from our daily diet serves to be an effective way to combat the rising obesity issue worldwide. Hence, reducing fat content in mayonnaise, a high fat food product, is one of the primary trends in the food industry. To date, research on the use of nanocellulose, a new and emerging form of fat mimetic, in mayonnaise formulation remains limited. This study sets out to formulate reduced fat 5%, 15%, and 30% mayonnaise using varying concentration of nanocellulose synthesized from palm pressed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In vivo study of rats fed with NFC-modified cream further supported the inhibition of fat digestion with similar mechanisms (DeLoid et al, 2018). Moreover, Golchoobi et al (2016), Heggset et al (2020), and Lee et al (2022) reported on the improved rheological and organoleptic properties of low-fat mayonnaise upon the addition of NFC.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In vivo study of rats fed with NFC-modified cream further supported the inhibition of fat digestion with similar mechanisms (DeLoid et al, 2018). Moreover, Golchoobi et al (2016), Heggset et al (2020), and Lee et al (2022) reported on the improved rheological and organoleptic properties of low-fat mayonnaise upon the addition of NFC.…”
Section: Introductionmentioning
confidence: 65%
“…Electrophoretic light scattering method from Lee et al (2022) was followed to measure zeta potential by Nano ZS zetasizer (Malvern Panalytical Ltd.) at room temperature (25 • C). Dilution of emulsion samples with 20 mM sodium chloride solution was conducted to prevent multiple scattering effects.…”
Section: Zeta Potential Analysismentioning
confidence: 99%
“…Treatment • Bio-compatible bio-ink assisted the cell encapsulation at 5 million cells/mL cell density. [139] carried out in the present section makes clear the emerging and cutting-edge applications of NCs as rheology modulators in the coating [117] and paint industries [118] as well as a rheology modulator for cement, [119] composites, [118,[120][121][122] electronic devices, [122][123][124][125] cosmetics, foods, [117,[126][127][128][129][130] drilling fluids, [122,131] and so forth. The superior mechanical, shear thinning, and bio-compatible/non-cytotoxic qualities of NC have also piqued researchers' attention in developing 3D bio-printing materials for creating viable living human organs/tissues.…”
Section: Field Of Application Applicationmentioning
confidence: 92%
“…[ 84,120–149 ] Some of the top‐notch characteristics that specifically define the distinctive rheological features of NC suspensions and their ability to act as rheology modifiers in diverse applications include their large water retention/holding potential, remarkable shear thinning behavior, their capabilities to align at high shear rates, thickening impact, and their capacity to form thixotropic frameworks that excellent restoration phenomena. The literature review carried out in the present section makes clear the emerging and cutting‐edge applications of NCs as rheology modulators in the coating [ 117 ] and paint industries [ 118 ] as well as a rheology modulator for cement, [ 119 ] composites, [ 118,120–122 ] electronic devices, [ 122–125 ] cosmetics, foods, [ 117,126–130 ] drilling fluids, [ 122,131 ] and so forth. The superior mechanical, shear thinning, and bio‐compatible/non‐cytotoxic qualities of NC have also piqued researchers' attention in developing 3D bio‐printing materials for creating viable living human organs/tissues.…”
Section: Advanced Applications Of Nano Cellulose As Rheology Modifiersmentioning
confidence: 99%
“…Electrospinning is an easy, universal, and hopeful process to make continuous micro to nanofibrous films from polymers because of its unique fiber arrangements (Deng et al., 2018; Dodero et al., 2020). Nowadays, single‐fluid electrospinning (Lee et al., 2022; Wong et al., 2022) is being developed into multi‐fluid electrospinning techniques such as coaxial (Jiang et al., 2022), tri‐axial (Wang et al., 2020), parallel or side‐by‐side (Wang, Yu, et al., 2023), and other complex processes (Wang, Ge, et al., 2023) for employment in different fields. Coaxial electrospinning processes can generate core–shell nanofibers with an outer layer protecting unstable bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%